2019
DOI: 10.1146/annurev-conmatphys-031218-013144
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity and Superconductivity in Doped Strontium Titanate

Abstract: Strontium titanate is a wide-gap semiconductor avoiding a ferroelectric instability thanks to quantum fluctuations. This proximity leads to strong screening of static Coulomb interaction and paves the way for the emergence of a very dilute metal with extremely mobile carriers at liquid-helium temperature. Upon warming, mobility decreases by several orders of magnitude. Yet, metallicity persists above room temperature even when the apparent mean free path falls below the electron wavelength. The superconducting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 138 publications
(253 reference statements)
6
130
0
Order By: Relevance
“…17, are for the same films studied in this work. The phase diagram shows the well-known superconducting "dome" [1] in close proximity to the quantum critical point of the spontaneous ferroelectric order. In this region, the superconducting critical temperature is enhanced by up to a factor of two in comparison with identically doped strainfree films grown on SrTiO 3 substrates [17], highlighting the essential role played by the spontaneous ferroelectricity.…”
Section: Interplay Between Ferroelectricity and Superconductivitymentioning
confidence: 88%
See 1 more Smart Citation
“…17, are for the same films studied in this work. The phase diagram shows the well-known superconducting "dome" [1] in close proximity to the quantum critical point of the spontaneous ferroelectric order. In this region, the superconducting critical temperature is enhanced by up to a factor of two in comparison with identically doped strainfree films grown on SrTiO 3 substrates [17], highlighting the essential role played by the spontaneous ferroelectricity.…”
Section: Interplay Between Ferroelectricity and Superconductivitymentioning
confidence: 88%
“…Despite its long history and contemporary interest, the superconducting phase of SrTiO 3 is still not well understood [1]. A central open question is how the superconductivity emerges from an exceptionally dilute Fermi gas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this quantum paraelectric can become a dilute metal (with a carrier concentration as small as ≈ 10 16 cm −3 ) upon oxygen reduction [16,17]. The dilute metal undergoes a superconducting transition below 0.3 K [18][19][20]. Rischau et al have recently found that a superconducting phase coexists with a FE-like instability in ndoped Sr 1−x Ca x TiO 3−δ and superconductivity and ferroelectricity (FE) may be intimately linked [21].…”
Section: Introductionmentioning
confidence: 99%
“…For non-local potentials satisfying Eqs. (3), no such ad-hoc regularization is needed: the integral in Eq. (4) is mathematically well-defined [21].…”
mentioning
confidence: 99%